Market Anomalies : January Effect in Indonesia Stock Exchange, Kuala Lumpur Stock Exchange And National Stock Exchange Of India Period 2016-2020 - Komariah, Siti; Nursihab, Aris; Rimantari, Nur Endah; Juniar, Nurul Aini; Herlina, Ulfa; Maulana, Fery Septiyadi (CENTRAL ASIA AND THE CAUCASUS, 2022)
There is a lot of information which can affect stock price movements in the capital market. This information is often overreacted by the investors in making investment decisions. It often happens at certain moments, including at the beginning of the year (January). The purpose of this research is to determine the January effect phenomenon on the Indonesia, Malaysia and India Stock Exchanges for the 2016-2020 period. In addition, to find out whether there are differences in stock returns between January and other months, and to find out whether there are differences in stock returns on the Indonesian, Malaysian and Indian Stock Exchanges during the research period. The data used is weekly major stock price index data from January 2016 to December 2020 with a total of 259 time series data. The research method used is a comparative method. The analytical techniques used are normality test, homogeneity test, ANOVA test, Post Hoc test, and Independent Sample T-test. The results showed that there was no January effect on the Indonesia Stock Exchange, Malaysia and India because there is no significant difference in the average value of stock returns between January and other months. The results of the stock return test show that there are differences in stock returns between the Stock Exchanges in Indonesia and India, and there are no differences in stock returns between the Stock exchanges in Indonesia and Malaysia.